Anatomical Studies and Evaluation of Genetic Stability in Plantlets Derived from Somatic Embryos of Arabica Coffee - Rina Arimarsetiowati; Budi Setiadi Daryono; Yohana Theresia Maria Astuti; Endang Semiarti (Bogor Agricultural University, Indonesia, 2023)
Anatomical characteristics regenerant plantlet of Arabica coffee (Coffea arabica L.) were observed to determine the difference of plantlet performance between Sigararutang and Maragogige grown in shooting and rooting medium. Transverse sections of the fresh roots, stems and leaves of three-month-old plantlets from somatic embryos were collected and used for the study. Sigararutang and Maragogipe as the plantlet materials were chosen based on the bean size and the origin. Stomata were microscopically observed on the abaxial leaf paradermal section. A conformity test to compare between plantlet and the parent plant was observed to perform genetic stability. Assessment of genetic stability was measured by using the sequence of trnL (UAA) region. The result showed that all the anatomical roots, stems and leaves of the Maragogipe plantlet have a greater number than Sigararutang (root diameter, cortex thickness, distance of long stele, distance of short stele, endodermis thickness, stem diameter, cortex thickness, maximum stele diameter, minimum stele diameter, epidermis thickness, diameter of stomatal closing, length of stomatal closing, total stomatal density, adaxial epidermis density, midrib thickness, adaxial epidermis thickness, abaxial epidermis thickness, diameter of the vascular bundles, lamina thickness), except of epidermis thickness, diameter of the vascular bundles, diameter of stomatal aperture, diameter of stomatal opening, length of stomatal opening and abaxial epidermis density. Taxonomists may be able to use these anatomic traits as supplementary proof in the determination of Arabica coffee. Molecular analysis showed that there were genetically identical organisms between the plantlet and the parent plant. It was indicated there was no somaclonal variation during somatic embryogenesis in the micropropagation of Arabica coffee.